FATAL PROPHECIES AND SIGNS OF FATE IN THE WORKS OF N.V. GOGOL (Web of Teachers: Inderscience Research, 2024)
This article delves into the recurring themes of fatal prophecies and signs of fate in the works of Nikolai Gogol. It examines how these motifs are employed in his literature to explore the human condition, societal norms, and the inevitability of destiny. Through analysis of select works such as "The Overcoat," "Taras Bulba," and "The Nose," this article explores the significance of these themes in Gogol's oeuvre and their lasting impact on Russian literature.